Role of Dietary Habit in Recurrences of Recurrent Aphthous Stomatitis - A pilot study - Aida Fadhilla Darwis; Amalia Retno Giantyana (TALENTA, 2024)
Recurrent aphthous stomatitis (RAS) is the most common oral mucosal disease characterized by oral inflammation with a variety of recurrences (â‰¥2 episodes) a year. The therapeutic goal includes the prevention of recurrences. Despite uncertain exact etiology of RAS, the decisive factors comprise nutritional deficiency and principal immunopathogenesis. These factors are related to nutritional intake adequacy which is reflected through dietary habits. Therefore, this study aimed to determine the relationship between dietary habits and recurrences of RAS patients at the Installation of Oral Medicine, Dental and Oral Hospital Universitas Sumatera Utara. An analytical survey was performed with a cross-sectional approach through a questionnaire. The population was 78 patients diagnosed between January 2018 and December 2019, based on the clinical medical record journal. In this study, analysis was conducted using the Chi-square test. The results showed that food intake (P=0.001) and dietary habits (P= 0.042) were significant, compared to food preferences (p = 0.064). In conclusion, a positive relationship existed between dietary habits and recurrences of RAS patients.